Sistema de automação microcontrolado: controle de irrigação controlado por arduino no cultivo de hortaliças - SOUZA, Eduarda Ferreira de (2025)
The automation provided by microcontrollers revolutionizes agricultural practices, such as irrigation control. Allowing the sensing of an environment, through the collection of temperature and humidity factors. That is, this capacity, combined with instant decision making through actuators, highlights the advantages of these systems, from energy efficiency in irrigation to the reduction of waste of water resources, contributing to more sustainable and technologically advanced agricultural practices. In this sense, the objective of this work is to develop a prototype of an irrigation system with automation based on an Arduino microcontroller for vegetable cultivation. The present work developed the prototype, as well as functionality tests in collecting temperature and humidity data.